Aspects of civilizational Islam - Shuriye, Abdi Omar (Islamic Centre for Research and Development, Australia, 2008)
Civilizational Islam is not a new religion, doctrine or sect. It is an idea which aims to draw the attention of the Malaysians and the world at the large to the correct understanding of the religion of Islam. In this paper the author studies two of ten principles of civilizational Islam. The paper argues that for the project to succeed it must be presented in a way that attracts Muslim policymakers, scholars as well as the non-Muslim world.